Protective effect of soy isoflavones and activity levels of plasma paraoxonase and arylesterase in the experimental nonalcoholic steatohepatitis model - Ustundag, Bilal; Bahcecioglu, Ibrahim Halil; Şahin, Kazım; Duzgun, Sevda; Koca, Suleyman; Gulcu, Funda; Ozercan, Ibrahim Hanifi (Springer, 2007)
Nonalcoholic steatohepatitis (NASH) is characterized by diffuse fatty infiltration in the liver and ballooning degeneration and inflammation in hepatocytes. We aimed to study the protective effect of soy isoflavones on experimental NASH and their effects on plasma paraoxanese and arylesterase levels in rats. Twenty-eight male rats were divided into four groups: Group 1 (n=7) received an isocaloric normal diet for 8 weeks, Group 2 (n=7) was fed an isocaloric basal diet plus oral soy isoflavone for 8 weeks (100 mg/kg in diet), Group 3 (n=7) received a special diet that was methionine and choline deficient (MCD) and rich in fat for 8 weeks, and Group 4 (n=7) was fed a special diet that was MCD and rich in fat plus oral soy isoflavone for 8 weeks (100 mg/kg in diet). Blood samples were collected to measure plasma malondialdehyde (MDA), paraoxanese, and arylesterase and biochemical parameters. Tissue samples were duly taken for histopathological examination and measurement of tissue MDA levels. Plasma MDA levels were higher in Group 3 than in Groups 1, 2, and 4 (P < 0.01, P < 0.05, and P < 0.05 respectively). Liver tissue MDA levels were also significantly higher in Group 3 compared to Groups 1, 2, and 4 (P < 0.001, P < 0.001, and P < 0.05 respectively). A significant decrease was found in the plasma and liver tissue MDA levels in Group 4 compared to Group 3 (P < 0.05 and P < 0.05, respectively). The activity levels of plasma paraoxanase and arylesterase were significantly higher in Group 2 than in Groups 1 and 3 (P < 0.05 and P < 0.01, respectively). Also, the plasma paraoxanase and arylesterase levels were significantly higher in Group 4 compared to Groups 1 and 3 (P < 0.05 and P < 0.01, respectively). A significant reduction was observed in Group 4 in steatosis, inflammation, necrosis, and fibrosis compared to Group 3 (P < 0.05 for each). We conclude that soy isoflavones seem to be effective in preventing liver damage by decreasing lipid peroxidation in the NASH model induced by a MCD diet. They stimulate and increase the activity of the antioxidative paraoxanase enyzme while decreasing the total cholesterol and triglyceride levels.
Keywords: nonalcoholic steatohepatitis; paraoxonase; arylesterase; soy isoflavone; methionine- and choline-deficient diet